Free and Open Source Codes for Computational Chemistry Research Initiation: A Conspectus - Adhikari, Jhashanath; Adhikari, Rameshwar (Journal of Nepal Chemical Society, 2023)
Computational chemistry is a field of current active research in science that can supplement and complement the regular experimental methods and validate or propose new theoretical formulations. It has contributed from basic to advanced levels of investigation in a synergistic manner. The mathematical experiments can be pursued with minimal resources and are sustainable making it a good approach for institutions with limited resources. The freely available computer programs that are suitable for solving various types of problems in chemistry and interdisciplinary areas are briefly mentioned. The general features and specificity of some selected codes that are adaptable for undergraduate and graduate-level courses and research in Nepal are highlighted. A recommendation is made for the incorporation of adequate theoretical courses and parallel laboratory sessions in the existing syllabus for obtaining a trained and skilled workforce qualified for national and global careers in computational chemistry and also for research and development in Nepal.